Influence of natural and accelerated weathering on the mechanical properties of low-density polyethylene films - Tuasikal, Muhammad Abduh; Alothman, Othman Y.; Luqman, Mohammad; Al-Zahrani, Saeed M.; Jawaid, Mohammad (Taylor & Francis, 2014)
Natural and accelerated weathering tests were performed to inspect the effect of antioxidants on low-density polyethylene (LDPE) films used as greenhouse covering materials. The LDPE pellets were extruded and blown into a film using a twin-screw extruder and film blowing machine, respectively. The film with 0.2 wt.% Alkanox-240 (AN-0.2) stabilizer showed the highest tensile strength (11 MPa) among all samples during 90 days of natural as well as accelerated weathering. The elastic modulus of the film with 0.5 wt.% of Good-rite (GR-0.5) increased after weathering from approximately 91.8 to 138.9 MPa, and showed the best performance. Morphological images of the neat LDPE film during weathering showed some cracks and grooves, while those of stabilized films showed fewer cracks. Moreover, the estimation of the rapidity of the accelerated method compared to the natural one was approximately nine times faster in Riyadh during the summer season (June–August). The present study suggests that the addition of antioxidants can improve the tensile strength, stability, and, hence, the effectiveness of these films. The best antioxidants were found to be 0.2 wt.% Alkanox and 0.5 wt.% Good-rite antioxidants.